Political embeddedness in environmental contexts: the intersections of social networks and planning institutions in coastal land use. Issue 2 (3rd April 2018) - Scott, Michael; Balaev, Mikhail; Clarke, Beverley
ABSTRACT: Despite well-documented climate change risks, coastal developments are still built. This article argues that the success or failure of development approval is conditioned by political embeddedness: the intersections of social network and institutional power. By synthesizing Granovetter's theory of structural embeddedness with a Polanyian account of land's institutional embeddedness in protective zoning, two-mode social network analysis methods are utilized to explore how both forms of embeddedness influence development processes. Comparing two South Australian case studies of an apartment complex and a surf club development, we illustrate how influential social actors emerge from within land use institutions, who then occupy network positions to co-ordinate the exercise of power between, and through, organizations. This theoretical approach to political embeddedness brings back in a finer-grained appreciation of how power is actively practised through the uneven social topography arising out of land use zoning. An implication of these findings is greater analytical attention should be given to how different land use zonings open divergent lines of contest in attempts to achieve more environmentally just outcomes. By doing so, we call for a sociologically informed conceptualization of political embeddedness in environmental studies, which is in contrast to current theoretical and methodological eclecticism.